STRUCTURE OF SINGLE-STAGE DENTAL IMPLANTS FOR VARYING DEGREES OF ALVEOLAR ATROPHY (World Bulletin of Public Health, 2022)
Lack of teeth impairs the vital function of the body - chewing of food, which affects digestive processes and causes the development of other diseases. The state of teeth, periodontium and mucous membrane of the oral cavity is connected with the state of other parts of the gastrointestinal tract, as well as other systems of the body (locomotor system, cardiovascular system, endocrine system), higher nervous activity, infectious diseases, cancer, quality of sleep, obesity and the state of general defence forces. Periimplantitis and one of the reasons for its appearance may be the connection between implant and abutment and cavities in it. This problem can be minimised but not eliminated in demountable implants, and the penetration of micro-organisms into the internal spaces of the implants seems inevitable.
Keywords: radiography; odontometry; height of bone